Abnormal Somatosensory Temporal Discrimination Is Not Related to Impaired Fine Motor Skills in Carpal Tunnel Syndrome - Aliş, Ceren; Ayas, Selahattin; Zileli, İsmail and Uzun Adatepe, Nurten and Karaali Savrun, Feray and Gündüz, Ayşegül (Cerrahpaşa Medical Journal, 2023)
Objective: Carpal tunnel syndrome has been shown to cause hand clumsiness, impairment in pinch grip force, and fine motor skills. We hypothesized that impaired fine motor skills in carpal tunnel syndrome may be related to maladaptive central somatosensory changes. This study aimed to investigate the relationship between the changes in central sensory pathways and fine motor activities in patients with carpal tunnel syndrome by examining the somatosensory temporal discrimination threshold. Methods: This study included 37 patients with idiopathic carpal tunnel syndrome and 19 healthy subjects. After recording routine nerve conduction studies, sensory threshold and somatosensory temporal discrimination threshold on volar faces of dominant second (2f) and fifth fingers (5f) were determined. All patients performed 9-hole peg test. We also questioned the presence of dropping objects. Results: Object dropping was more frequent in patients with idiopathic carpal tunnel syndrome in comparison to healthy subjects (P = .000). Duration to complete 9-hole peg test was also higher in patients with dropping objects. Although sensory threshold-2f and somatosensory temporal discrimination threshold-2f were higher in patients with carpal tunnel syndrome compared to healthy subjects, somatosensory temporal discrimination threshold- 2f was not related to dropping objects. The duration of 9-hole peg test did not correlate with somatosensory temporal discrimination threshold-2f. Conclusion: We showed that there was a maladaptive reorganization process in primary somatosensory cortex of 2f represented by somatosensory temporal discrimination threshold in patients with carpal tunnel syndrome. Fine motor skills may be due to the disruption of superficial touch sensation or motor dysfunction secondary to carpal tunnel syndrome, but it is not related to maladaptive changes in somatosensory cortex-basal ganglia network represented by somatosensory temporal discrimination threshold. Cite this article as: Aliş C, Ayas S, Zileli I, Uzun Adatepe N, Karaali Savrun F, Gündüz A. Abnormal somatosensory temporal discrimination is not related to impaired fine motor skills in carpal tunnel syndrome. Cerrahpaşa Med J. 2023;47(1):72-76.